Factors to Effective Clinical Experience, Willingness to pursue Career in Rural Health Facilities among Nursing Students on Clinical Placement in Southeast Nigeria and Rural Development - O. Abah , George; O. Okafor, Samuel; Anyoko-Shaba, Orkuma; C. Nnamchi, Onyedikachi; O. Ọkop, Ekaette; Ogunleye, Akindele (Investigación y Educación en Enfermería, 2024)
Objective. To describe the Factors to Effective Clinical Experience and Willingness to pursue Career in Rural Health Facilities among Nursing Students on Clinical Placement in southeast Nigeria. Methods. The study was conducted among 48 rural health centres and general hospitals with 528 respondents from different higher institutions of learning serving in these health facilities for their clinical experience. The study applied survey design and utilized questionnaire instrument for data collection. Results. Majority of the students (60%) agreed that their school lacked functional practical demonstration laboratory for students’ clinical practice, 66.7% agreed that their school lab lacked large space for all the students to observe what is being taught, 79.9% that their school lab lacked enough equipment that can enable many students to practice procedures; majority of the students (79.9%) answered that the hospitals where they are on clinical placement lacked enough equipment needed for the students on each shift of practice, 59.9% agreed that student/client ratio in each ward during clinical experience periods was not enough for students' practice under supervision, while 73.3% indicated that their school lacked library with current nursing texts for references. Personal, socioeconomic and institutional factors explain the 76% of the variance of effective clinical experience and the 52% of the variance of the willingness to work in rural health facilities in the future if offered employment. Conclusion. The factors surrounding effective clinical experience in rural healthcare facilities in southeastern Nigeria are unfavorable and could discourage future nurses from working there. It is necessary to implement strategies to improve the management of these centers in order to promote the perspective of improving sustainable rural health in this region.